Association of Pre-Procedure Microalbuminuria with Development of Contrast-Induced Nephropathy among Patients with Acute Coronary Syndrome Undergoing Percutaneous Coronary Intervention - Hasan, Md. Kamrul; Badiuzzaman, Mohammad; Masum, AKM Mohiuddin Bhuiyan; Hasan, K.A.M. Mahbub; Adnan, Tanvir; Siddika, Ayesha; Ali, Syed Mahmud; Hasan, Nahidul; Chowdhury, Shamim (Cardiology and Cardiovascular Medicine, 2026)
Patients undergoing percutaneous coronary intervention (PCI) are at high risk for development of contrast induced nephropathy (CIN). Urinary albumin excretion is one of the earliest biomarkers of kidney injury and it is associated with deterioration of renal function after PCI in the patients with acute coronary syndrome (ACS). The aim of this study was to assess the relation between pre procedure microalbuminuria and development of CIN among the patients with ACS undergoing PCI. This Cross-sectional analytical study was carried out in the department of cardiology, National Heart Foundation Hospital and Research Institute from August 2021 to July 2023 (one year). This study assigned 164 consecutive patients present with ACS undergoing PCI and categorized into two groups according to albumin excretion status Microalbuminuria and Normoalbuminuria. Microalbuminurea (MA) is defined as urinary Albumin-creatinine ratio (UACR) of 30- 300mg/gm creatinine in random spot urine sample. Effectiveness of relation between pre procedure microalbuminuria and development of CIN was analyzed using a receiver operating characteristic (ROC) curve. In this study out of 164 patients,67(41%) patients were microalbuminuria and 97 (59%) were normoalbuminuric. Mean Urinary ACR was found 73.75 ±5.6 in microalbuminuria group and 16.24 ±6.43 in normoalbuminuria group. In microalbuminuria group CIN was developed in 24 (36%) patients and CIN did not develop in 43 (64%) patients, in normoalbuminuria group 15 (16%) patients had developed CIN and 82 (84%) patients did not develop CIN. Receiver-operator characteristic (ROC) were constructed using urinary ACR of the patients with CIN positive, which gave a urinary ACR cut off value of (≥23.17mg/g) as the value with a best combination of sensitivity and specificity for CIN positive were found to be 74.0% and52.8% respectively. Microalbuminuria is an important biochemical parameter for prediction development of CIN among patients with ACS undergoing PCI.